Maternal pre-pregnancy body mass index and foetal acidosis in vaginal and caesarean deliveries: The Japan Environment and Children’s Study - Tsuyoshi Murata (Nature Portfolio, 2021)
Abstract A high maternal body mass index (BMI) is associated with increased risks of asphyxia-related neonatal morbidity. We evaluated the association between maternal pre-pregnancy BMI and foetal acidosis while accounting for the mode of delivery. Participants from the Japan Environment and Children’s Study with singleton pregnancies after 22 weeks of gestation who gave birth during 2011–2014 were included. The participants (n = 71,799) were categorised into five groups according to the pre-pregnancy BMI: G1 (BMI < 18.5 kg/m2), G2 (18.5 to < 20.0 kg/m2), G3 (20.0 to < 23.0 kg/m2), G4 (23.0 to < 25.0 kg/m2), and G5 (≥ 25.0 kg/m2). Foetal acidosis was defined as umbilical artery pH (UmA-pH) < 7.20 or < 7.10. Multiple logistic regression analyses were used to evaluate the effect of pre-pregnancy BMI on foetal acidosis risk, accounting for the mode of delivery. In Japanese women, pre-pregnancy BMI ≥ 25.0 kg/m2 significantly increased the likelihood of foetal acidosis in newborns delivered vaginally. We found no association between pre-pregnancy BMI and foetal acidosis in newborns delivered via caesarean section. Counselling for body weight control before pregnancy and adequate management and selection of the mode of delivery in pregnant women with a high BMI who are in labour may be essential to avoid foetal acidosis.